Substantiation of the approach to the formation of the crews in rowing - Iakovenko, O. O. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The principles of the selection of athletes for the crews' formation in foreign countries were considered, and the most informative criteria for the selection of rowers from one team were identified. The analysis of regulatory documents of rowing teams in foreign countries was conducted. In the course of this analysis were detected the top countries in this kind of sport and found that it is fundamentally important for a comprehensive approach to the selection of athletes for the formation of the crew. It is noted that the use of the principle of comprehensiveness is a key factor in the selection system and contributes to the achievement of high results in the international sports arena. A system of selection in terms: the result of competitive activity in the smaller classes of vessels, functional, technical and physical performance.